\(~~~HD~~~\)
\(\frac{90}{93}=1-\frac{3}{93};\frac{190}{193}=1-\frac{3}{193}\)
Vì: 93<193 nên: \(\frac{3}{93}>\frac{3}{193}\Rightarrow\frac{90}{93}< \frac{190}{193}\)
Vậy: \(\frac{90}{93}< \frac{190}{193}\)
ta có :
\(\frac{90}{93}< \frac{190}{193}\)
\(\frac{90}{93}=\frac{190}{193}\)
Vì \(\frac{90}{93}=\frac{190}{193}\)bỏ số 1 đi thì bằng \(\frac{90}{93}=\frac{90}{93}\)
Hk tốt
k nhé
ta có : 190/193 = 100 + 90/ 100+ 93 = 100/100 + 90/93 = 1 + 90/93
mà 1+ 90/93 > 90/93 => 190/193 > 90/93
( mình ko biết viết thành phân số , hi vọng bạn hiểu )